Investigating the possibility of consensus from the perspective of Imami jurisprudence - Mohammad Mahdi Esmaelpour; Mohammad Hasan Haeri; Mohammad Taghi Ghabooli (مطالعات فقه و حقوق اسلامی)
At first glance, it may seem that many Imami jurists take the possibility of consensus for granted, while this will depend on our accepted definition of consensus and the basis of its authority. With definitions of consensus based on sense, conjecture, and grace, it is usually impossible for that to happen. From the author's point of view, it is impossible for all jurists in all ages with different tastes and intellectual backgrounds to issue fatwas in matters for which there is no valid evidence from verses and hadiths, and in case of such an agreement, a reassuring solution to know the fatwa. Not all jurists will exist. It seems that only if we accept the authority of consensus on the basis of reason, its occurrence will be in the position of proof and proof without hindrance, because in this case it is not necessary to study the opinion of all jurists, but the consent of most jurists or The famous people in the on the subject of consensus and the absence of the opposite promise ensures that the shari'ah agrees with on the subject of consensus. This research tries to examine the possibility of realizing consensus by re-reading the accepted definitions of consensus among Imami jurists and the principles of its authority.